La desnutrición infantil y su influencia en el desarrollo cognitivo en los niños y niñas del primer año de educación básica de la escuela fiscal mixta Gaudencio Vite Ortega del cantón Santa Rosa, provincia de El Oro, periodo lectivo 2011 - 2012. - Severino Mogollón, Digna Emérita (2015)
This research report is based on the study of influence of malnutrition on cognitive development in children , where parents of families and teachers know about the importance of maintaining adequate food and how this affects negatively in the educational process of students.